Die messiaanse aard van psalms: hoe dit ’n Nuwe-Testamentiese lees, vertaling en omdigting van die psalms raak - J. L. Helberg (emeritus) (In die Skriflig, 2006)
The messianic character of the psalms: how it affects a New Testament reading, translation and re-versification of the psalms The 2001 re-versification of the psalms as well as the 1983 translation in Afrikaans is rejected by some, because the messiah is not rendered in capital letters. This article views the matter from the perspective of Psalm 1 and 2 as an introduction which characterises the whole psalter as messianic. This article explores what this means. The relation between Psalm 2 (re kingship) and Psalm 1 (re the Law/Word of Yahweh) is in- vestigated in able to view the “messianic” concept in its real perspective. The same applies to the relation Old Testament- New Testament and expectation-fulfilment. The regenerative character of the fulfilment in Christ as well as its implication for one’s inclination towards one’s neighbour and how it affects that of the psalmists is explored. The conclusion of the article is that to render the messiah in capital letters in the psalms is to bypass the regenerartive fulfilment by Christ and to ignore the implication thereof regarding enemies.